Terapi Pemberian Cairan Dengan DHF Pada An.R. - Gilang, Surya Gilang Ramadhan; Handayani, Reska; Maidawilis; Sari, Putri Minas (Jurnal Keperawatan Medika, 2025)
Dengue Hemorrhagic Fever (DHF) is a serious infectious disease in Indonesia, especially for children. Their immature immune systems make children vulnerable to DHF complications. This case study applies the nursing care provided to An. R., who had DHF, in the Marwa Room at Aisyiyah Hospital in Pariaman City. The case study uses a nursing process that includes assessment, diagnosis, planning, implementation, and evaluation. The assessment revealed that the child had a high fever and exhibited signs of dehydration and bleeding manifestations, such as petechiae. Nursing diagnoses determined included hypovolemia, hyperthermia, acute pain, and risk of nutritional deficits. Interventions included hyperthermia management, fluid administration, vital sign monitoring, family education, and supportive therapy. An.R.'s temperature, vital signs, and appetite all improved. Nursing care plays an important role in supporting the healing process of children with DHF. This case study highlights the role of the family and the environment in patient recovery and disease prevention. This involves improving environmental hygiene through regularly draining water reservoirs, closing water reservoirs tightly, and burying used items that can collect rainwater. These measures prevent mosquito breeding.